P693 Willingness and hesitancy to the telemedicine in patients with inflammatory bowel disease during COVID-19 outbreak. Preliminary results of a survey in an Italian IBD Center. (21st January 2022) - Bossa, F; Guerra, M; Carparelli, S; Antonella, M; Terracciano, F; Costantino, A; Caprioli, F; Valvano, M R; Martino, G; Nardella, M; Perri, F
Abstract: Background: Telemedicine is becoming a necessary tool for chronic disease management. Thanks to the wide diffusion of devices connecting to the World Wide Web, a large part of the population are now able to access to telemedicine services.Telemedicine is becoming a necessary tool for chronic disease management. Thanks to the wide diffusion of devices connecting to the World Wide Web, a large part of the population are now able to access to telemedicine services. The aim of this survey was to explore the willingness and hesitancy of patients with inflammatory bowel disease (IBD) to the use of telemedicine during COVD-19 outbreak. Methods: A paper-and-pencil questionnaire was proposed to all consecutive patients observed at our tertiary IBD center in San Giovanni Rotondo (Italy) from February to May 2021. The survey investigated 20 items that can be grouped into 5 areas: socio-demographic data, clinical data, informatics competence, devices and network utilized for the internet connection, attitude to the telemedicine, and the impact of COVID-19 pandemic. Results: A total of 156 patients completed the questionnaire (100 males). One hundred forthy-three patients (91.7%) were under 65 years and only 15 (9.6%) were graduates. Forthy-seven patients (30%) were single, 101 married (65%). Eighteen patients (11.5%) felt they had no IT skills. Eight patients (5.1%) had a previous experience of telemedicine. One hundred twenty-three patients (78.8%) consider the support of telemedicine useful for the management of their pathology and 134 (85.9%) would like the Center where they are followed up to have the possibility of offering a telemedicine service. One hundred three patients (66.0%) would like to have a teleconsultation with figures other than the Gastroenterologist. Ninety-seven patients (62.2%) agree that the ongoing coronavirus pandemic has a major impact on the need to implement telemedicine. Regarding the confidence with telemedicine, 106 patients (67.9%) were partially or totally agreeing telemedicine can properly resolve health problems, and 98 (62.8%) agree that technologies guarantee the privacy of the health data. One hundred twenty-five patients (80%) agree that telemedicine should be developed independently of the pandemic, however only 48 patients (31%) believe that telemedicine guarantee the same level of assistance of visit in presence. Conclusion: Italian IBD patients showed a positive attitude towards telemedicine and consider that useful for the management of their disease. The majority of patients would like the center where they are followed up offering a telemedicine service, regardless of the ongoing pandemic. However only one third of patients believe that telemedicine can offer the same level of assistance of in-presence visit.